CASE STUDY: THE EFFECTIVENESS OF ANKLE PUMP EXERCISE AND WARM COMPRESSES IN REDUCING THE DEGREE OF LEG OEDEMA IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD) - Dian Ayu Palupi; Hikmi Muharromah Pratiwi; Arif Setyo Upoyo (International Journal of Biomedical Nursing Review, 2025)
Introduction: One of the most common clinical manifestations in CKD patients is leg oedema. Oedema that is not treated promptly leads to several complications such as ischaemia due to reduced tissue function, reduced mobility, skin infections such as cellulitis or ulcers in chronic oedema. Oedema can be managed with non-pharmacological therapies such as a combination of ankle pumping and warm compresses. Purpose: This study aims to describe the reduction in the degree of leg oedema in patients with CKD after administration of ankle pump exercise and warm compresses. Methods: This research is a case study with a nursing approach to CKD patients with oedema. Participants in this study were 3 CKD patients with leg oedema. Interventions were carried out on 3 consecutive days within 15-20 minutes of each session. Pre- and post-measurements of the degree of oedema were made at each session. Discussion: Oedema is a condition resulting from an increase in hydrostatic pressure in the blood vessels, which causes the veins to become blocked and plasma fluid to accumulate in the interstitial spaces. The results of the measurement of the degree of oedema showed that two participants experienced a decrease in the degree of oedema from degree 3 to 2 and one participant experienced a decrease from degree 2 to 1. Conclusion: A combination of ankle pump exercise and warm compresses can reduce the degree of leg oedema in patients with CKD and can be used independently by patients and families.